The Pathophysiology Gastroesophageal Reflux Disease - Bradley Jimmy Waleleng; Marcellus Simadibrata; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
ABSTRACT The incidence of Gastroesophageal Reflux Disease (GERD), especially in Indonesia, is increasing with the change of community life-style. Also, the doctors’ perception in understanding clinical manifestation of GERD is alike in addition to the development of diagnostic facilities such as endoscopy in Indonesia. The GERD incidence in Indonesia is as high as the incidence in developed countries. Esophageal reflux develops in physiological condition, which may be found in normal individual. GERD development is caused by anatomical and physiological disorders such as hereditary or acquired factor; and other factors that may be categorized into offensive factors such as gastric acid, pepsin, bile acid, trypsin and disturbance in defensive factors such as hypotensive Lower Esophageal Sphincter (LES), Transient Lower Esophageal Sphincter Relaxations (TLESR), hiatal hernia, disrupted saliva production, esophageal peristaltic disorder; as well as other factors such as genetic, diet, or certain drugs. Imbalance of such factors may cause pathological repeated esophageal reflux which may damage esophageal mucosa and lead to GERD development including all of complications.   Keywords: esophageal reflux, GERD, LES